Higher-order resonant electronic recombination as a manifestation of configuration interaction - Beilmann, Christian; Amaro, Pedro; Bekker, Hendrik; Harman, Zoltán; Crespo López-Urrutia, José Ramon; Tashenov, Stanislav (Physica scripta, 2013)
Theoretical and experimental investigations of higher-order electron-ion recombination resonances including inter-shell excitations are presented for L-shell ions of Kr with the aim of examining details of atomic structure calculations. The particular importance of electron-electron interaction and configuration mixing effects for these recombination processes enables their use for detailed tests of electron correlation effects. A test of the required level of considered mixing configurations is presented and further experiments involving higher-order recombination channels are motivated.